198k views
12 votes
Expand 3a(a- 4b) pls help ​

User Jdhurst
by
4.9k points

1 Answer

11 votes

Hey there!

All you have to do is DISTRIBUTE

Here’s the formula:

a(b + c) = a(b) + a(c) = ab + ac

NOW LETS SOLVE FOR YOUR QUESTION

• 3a(a – 4b)

• 3a(a) + 3a(4b)

• 3a(a) = 3a² ⬅️ FRONT number

• 3a(4b) = 12ab ⬅️ BACK number

• Answer: 3a² + 12ab ☑️

Good luck on your assignment and enjoy your day!

~LoveYourselfFirst:)

User Flavaflo
by
5.2k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.